Mitral Annular Plane Systolic Excursion (MAPSE) as a Predictor of Atrial Fibrillation Recurrence in Patients after Pulmonary Vein Isolation - Jan Alatic; David Suran; Damijan Vokac; Franjo Husam Naji (Cardiology Research and Practice)
Introduction. Catheter ablation (CA) with pulmonary vein isolation (PVI) has become widely used in the past years for the treatment of atrial fibrillation (AF). Mitral annular plane systolic excursion (MAPSE) is the parameter that measures left ventricular longitudinal function, and it appears to be a good early marker of LV dysfunction. It is practically independent of poor image quality. The aim of our study was to analyse the role of echocardiographic variables, especially MAPSE in predicting the outcome of CA in patients with AF. Materials and Methods. We prospectively included 40 patients with paroxysmal and persistent AF that were referred for CA. All patients underwent radiofrequency CA with PVI. Standard transthoracic two-dimensional echocardiography was conducted one day after CA. Demographic data and the patients’ characteristics were noted. The endpoint of our study was to estimate the AF recurrence rate diagnosed by ECG within 6 months of the follow-up period. Results. 40 patients, mainly male (67.5%) with an average age of 61.43 ± 8.96 years were included in our study. The majority of patients had paroxysmal AF prior to ablation (77.5%). The AF recurrence rate was 20% after 6 months of follow-up. Lateral MAPSE in the AF-free group was greater than those who relapsed (1.57 ± 0.24 vs. 1.31 ± 0.25; p=0.012). Patients who remained AF-free after a 6-month follow-up period had a significantly smaller left ventricular volume index (LAVI) than those who relapsed (34.29 ± 6.91 ml/m2 vs. 42.90 ± 8.43 ml/m2; p=0.05). We found a significant reverse relationship between LAVI and MAPSE (p=0.020). Conclusion. MAPSE and LAVI present risk factors for AF recurrence, specifically reduced MAPSE and larger LAVI, are related to AF recurrence after CA. In the future, MAPSE could play a significant role when predicting the CA outcome in patients with AF.